خواص وتقريب الدوال في صف الدوال (Latakia University Journal -Basic Sciences Series, 2017)
درسنا في هذه المقالة إحدى مسائل التحليل الدالي المتعلقة بإنشاء صف دالي جديد نرمز له بـالرمز انطلاقاً من تعريف كلٍ من صف دوال ليبيغ وصف دوال هولدر ومن ثم درسنا علاقات التداخل في هذا الصف والعلاقة بين الصف الجديد وكلٍمن صفي دوال ليبيغ ودوالهولدر، في النهايةندرستقريب صف الدوال الجديد إلى دوال كسرية.We study in this paper one of functional analysis problems, involved with construction a new class of functions, denoted by . The definition of the new class depends on definition of Lebesgueclass of functions and on the Holder class . We study the relation between the new class and and approximation of the new class to rational functions.